STRUKTUR HEMIRING - Noviliani Noviliani; Saman Abdurrahman; Na'imah Hijriati (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2021)
Hemiring is a non-empty set  which is equipped with the addition operation " " and the multiplication operation " " and satisfied four conditions, namely:  is a commutative monoid with an identity element of ,  is semigroup, satisfied distributive properties the multiplication over addition on both sides, and satisfied    for each . There are several types of hemiring such as idempotent hemiring, zerosumfree hemiring, simple hemiring and others. In this paper, it discusses the sufficient and necessary conditions of a hemiring that is said to be commutative and said to be simple, prove the characteristics of the operation in zerosumfree hemiring, idempotent hemiring, and simple hemiring.